Social Media Marketing and Brand Loyalty in the Indonesian Fashion Market: Mediating Role of Consumer Brand Engagement and Brand Awareness - Renny Christiarini; Natalya Natalya; Lily Purwianti (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2025)
Purpose: This study examines how social media marketing elements—entertainment, interaction, and electronic word-of-mouth (eWOM)—influence brand loyalty toward local Indonesian fashion brands. It explores both the direct and indirect effects, with consumer brand engagement and brand awareness acting as mediators.Method: A quantitative research design was employed, involving 311 respondents aged 18–43 who are active social media users and have purchased local fashion products. Data were collected through an online questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM).Result: The results indicate that entertainment, interaction, and eWOM significantly enhance consumer brand engagement and brand awareness. Both mediating variables were found to strengthen brand loyalty, demonstrating that a well-structured and engaging digital presence can foster emotional connections, trust, and long-term relationships between consumers and local brands.Practical Implications for Economic Growth and Development: By enhancing their digital engagement strategies, local fashion brands can increase repeat purchases, generate sustainable revenue streams, and contribute to the growth of Indonesia's creative economy. These improvements also enhance the competitiveness of local brands in both domestic and global markets, supporting inclusive economic growth and industry resilience.Originality/Value: This study integrates entertainment, interaction, and eWOM into a single model. It also highlights the mediating roles of consumer brand engagement and brand awareness, specifically within the context of local Indonesian fashion brands targeting Gen Z and millennial consumers.